Implementation of Local Cultural Values in the Formation of National Character and Culture Based in the School Environment: Implementasi Nilai-Nilai Budaya Lokal dalam Pembentukan Karakter dan Budaya Bangsa Berbasis Budaya di Lingkungan Sekolah - Ulah, Mirna Safridatul; Suwarta, Nyoman; Fitriyah, Anis; Akmaliyah, Siti Nisaaul; Tsaqif, Itqon (Universitas Muhammadiyah Sidoarjo, 2024)
Education is a tool to shape the character and identity of the nation's next generation, because education creates quality of the young people, high knowledge, broad insight, and able to compete in global developments. The purpose of this study is to analyze the implementation of local cultural values in the formation of national character and culture based on the school environment. Using qualitative methods, data were obtained through observation, in-depth interviews and interpretation of events, using human instruments. The results of the analysis explain the implementation of local culture that has been applied in schools include: traditional food, local traditional toys and dances, wearing traditional East Java clothes, making miniature traditional houses, routine Istighosah every month, singing folk songs, banjari extra-curricular activities, tahfidz juz 30, habituation of 5S application, dhuhur prayers in congregation, salim/kiss hands when meeting parents, friendly prayers, art, and local cultural values. There are student self-development activities at school, including: Scouts, Flag Ceremony every Monday, commemoration of state holidays, wearing batik clothes on the first week of every month. Barriers to the implementation of local cultural values in character building and national culture in the school environment include: limited resources, time, environment, family, and friends.